Analisis Kasus Laporan Keuangan PT. Indofarma Tbk - Armein, Rizka Ardhianty (LAW REVIEW, 2005)
PT Indofarma Tbk is a company working in the area of supplying medicine and other  medical equipment or facilities for public use and benefits. In its Financial Report of the  year 2001, the company did something that according to the existing law is considered  a fraud. The company conducted a misleading information through marking up the  financial status in that report, in which it claimed to have been making big profit but in  reality, it suffer big loss. The Government Institution for Investment Affairs (Bapepam) found out this deceitful action and instantly appointed public accountant to audit the company. The company reasoned that the report was meant to be for internal use and in order to obtain more credit funds from bank. Furthermore it argued that it is legal because the asset considered by bank for credit approval does not include profit or loss made during the past year.